Large magnetocaloric effect and refrigerant capacity in Gd–Co–Ni metallic glasses - Yu, Hongyu (2013)
The thermal stability, magnetocaloric effect, and refrigerant capacity (RC) of Gd–Co–Ni metallic glasses were investigated. These alloys possess high glass transition temperature and crystallization temperature as well as a relatively wide supercooled liquid region ΔTx(ΔTx = Tx − Tg) (40–55 K). With increasing the Co/Ni ratio, the Curie temperature TC of the amorphous Gd–Co–Ni increases from 140 K to 192 K. For a magnetic field change of 0–5 T, the maximum magnetic entropy change (−ΔSMmax) and RC values are in the range of 6.04–6.47 J kg−1 K−1 and 450–502 J kg−1, respectively. These values are comparable with that of La(Fe0.88Si0.12)13 and higher than those for the well known magnetic refrigerant Gd5Si2Ge1.9Fe0.1 alloy. The large magnetic entropy change and refrigerant capacity as well as high thermal stability make the alloys attractive candidates as magnetic refrigeration materials for service temperatures of 100–230 K.